2020
DOI: 10.1111/jan.14653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aloe vera in adults with mucocutaneous problems: A systematic review and meta‐analysis

Abstract: Aims To analyse the different types of Aloe vera (AV) effects on various mucocutaneous problems among adults. Design A systematic review and meta‐analysis. Data Sources An exhaustive scanning of PubMed, Medline, ScienceDirect, and Google Scholar databases was conducted from January 2000–December 2019. Review Methods Randomized controlled trials (RCTs) publishing reports on the effects of AV in various mucocutaneous problems, psoriasis, burn, wound‐healing were included. The standardized mean differences (SMD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Recent evidence is available regarding the topical application of natural products, including honey, aloe vera (AV), bovine colostrum (BC) and others [14,15]. These composite agents contain a wide variety of biologically active substances such as lactoferrin, lactoperoxidase, growth factors, immunoglobulins, cytokines, iron, folic acid, electrolytes and vitamins, which may interfere with the pathobiological pathway underlying OM [16][17][18]. The beneficial effects of these agents on mucosal healing have already been described as mainly attributable to their immune-modulatory, anti-inflammatory and antibacterial activity [14,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence is available regarding the topical application of natural products, including honey, aloe vera (AV), bovine colostrum (BC) and others [14,15]. These composite agents contain a wide variety of biologically active substances such as lactoferrin, lactoperoxidase, growth factors, immunoglobulins, cytokines, iron, folic acid, electrolytes and vitamins, which may interfere with the pathobiological pathway underlying OM [16][17][18]. The beneficial effects of these agents on mucosal healing have already been described as mainly attributable to their immune-modulatory, anti-inflammatory and antibacterial activity [14,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Literature search returned controversial ndings of aloe vera in OM prevention. A previous study showed that aloe vera had healing activity to different mucocutaneous problems [21]. While a meta-analysis found aloe vera mouthwash showed no superior effect on OM prevention, compared with other natural products, such as honey, chlorhexidine and curcumin.…”
Section: Discussionmentioning
confidence: 98%
“…The beneficial effects of AV and of BC on wound care have been suggested by some preclinical studies [ 41 , 67 , 68 ]. Their effects on mucocutaneous issues such as pain reduction, wound healing acceleration, stomatitis healing, and QoL improvement are well known [ 42 , 43 , 51 , 52 ]. It has been suggested that some components of BC, such as nucleotides, epidermal growth factor (EGF), and insulin-like growth factor-1 (IGF-1), promote mucocutaneous cellular growth and also help repair gene impairment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aloe vera (AV)-based preparations contain various active compounds, including iron, folic acid, electrolytes, and vitamins, that have positive effects on general health [45][46][47][48]. Its formula shows emollient, moisturizing, antiinflammatory, and immune-modulatory properties [49,50], and has been studied for the prevention and treatment of several mucocutaneous conditions, without any adverse effects [51,52].…”
Section: Introductionmentioning
confidence: 99%